Mobile robot automation in warehouses. - Yildirim, Alp (Cranfield University, 2022)
Mobile robot systems are an automation solution in warehouses that make order fulfilment agile, flexible, and scalable to cope with customer orders' increasing volumes and complexities. Compared with manual operations, they combine higher productivity and throughput with lower operating costs. As the practical use of mobile robot systems increases, decision-makers are confronted with a plethora of decisions, but research is lagging in providing the needed academic insights and managerial guidance on the adoption and deployment of this novel technology. This PhD thesis aims to explain the mobile robot system implementation journey by conducting a mixed methods approach through three independent but interconnected papers. Paper 1 is based on a systematic literature review involving 107 papers from the literature. Paper 2 is a continuation of the systematic literature review to identify and evaluate available mobile robot systems in the market. It also offers mobile robot system selection approaches using the insights of five supply chain experts. Paper 3 is a multiple-case study involving four logistics functions from different countries. This thesis lists the potential motivations to adopt mobile robot systems. It offers multiple approaches to selecting an appropriate mobile robot system. It also provides a comprehensive adoption framework that elaborates on innovation diffusion theory and explains the entire mobile robot system adoption journey. Devising the phases of the mobile robot system adoption journey and categorising thirteen managerial decisions and nineteen contextual factors, this study offers guidance to supply chain managers and decision-makers.
Keywords: Supply chain management; case study; innovation adoption; automated guided vehicles; autonomous mobile robots; full-consistency method (FUCOM); innovation diffusion theory; technology-organisation-environment (TOE) framework